MOTIVASI KOREA UTARA MEMUTUSKAN HUBUNGAN KERJASAMA DENGAN KOREA SELATAN DI KAWASAN INDUSTRI KAESONG - Muhammad Farid Arpan; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research explains North Korea's motivation in terminating cooperative relations with South Korea in the Kaesong Industrial Complex. The end of cooperation is marked by the closing of Kaesong Industrial Complex in 2013. This research used qualitative methods, and used case as a strategy in this research. In this research, the data was collecting by used library research techniques where this techniques is collecting data sourced from the literature, like book, website, official publications, and journal. This research used mercantilisme perspective, with the theory of national interest. This research focused on nation-state as level analysis. This research shows that the closure of kaesong industrial area by north korea happened because the clash of interest between North Korea and South Korea. Besides, this research explain strategic value of Kaesong Industrial Complex and impact of the closing of this area.Keyword: Kaesong Industrial Complex, Closure, Strategic Value, Impact.